Comorbilidad y fragilidad de adultos mayores en tiempos de pandemia en establecimientos de salud, Iquitos 2022 - Del Aguila Silva, Kelly Carolina (2024)
Through a descriptive, cross-sectional and correlational study, the association between comorbidity and frailty of older adults in times of pandemic in health facilities in Iquitos was determined. The sample selected in a probabilistic manner was composed of 337 elderly people registered in the elderly programs of the health facilities. They were administered a sociodemographic questionnaire, perceived comorbidity and the Edmonton scale. The mean age of the older adults was 73.05 + 8.72 years, 59.3% were female, 37.1% were married, 43% had primary education, 34.7% lived in Iquitos and 68% had comprehensive health insurance. The 72.11% presented comorbidity, especially arterial hypertension and diabetes with an average disease time of 10.31+9.10 years. 55.5% were non-fragile older adults, 24.9% were frail vulnerable older adults, and 12.2% presented some degree of frailty. Age and morbidity indicators showed direct correlation with frailty; while education showed inverse correlation with frailty (p<0.01).